Prospects of "Slate Revolution" and Problem of Power Industry of China - M. Scryabina (Vestnik MGIMO-Universiteta)
The remarkable results of “shale gas revolution” in the USA have provoked a huge interest in Chinese energy circles. Beijing seriously considers the prospects of developing its abandoned domestic shale gas resources, which might result in a second “shale gas revolution”, this time in Asian region. Developing shale gas would help Beijing to bridge the gap between energy consumption and supply, and would also create a viable alternative to coal. However, the technology of shale gas extraction (hydraulic fracturing) is highly controversial, and raises a lot of concerns among environmentalists. “Fracking” has already been banned in a number of European states and there, and is a subject to moratorium in US states of New York, Connecticut and New Jersey. The core question is whether China can successfully adapt the extraction technology to its geologic conditions, and most importantly whether “fracking” of shale gas will help to alleviate the environmental degradation caused by rapid GDP growth, and help to increase energy security of Chinese economy.